Making Machines Safe for Humans: The Case of Siri - Guzman, Andrea L. (AoIR Selected Papers of Internet Research, 2013)
This paper explores cultural conceptions of human-machine communication through a discourse analysis of U.S. news media accounts of Apple’s launch of Siri – a voice-activated, personal assistant application. Through this analysis of online reports regarding Siri’s initial reception from 2 , 2 and 2 several themes emerge regarding the nature of Siri and communication with it. These themes portray Siri as the future made real; as part friendly female; as a futuristic servant at the users’ beck and call. In totality these portrayals establish Siri as the antithesis of malicious AI machines and position 2 as a non-threatening, technological slave firmly under the control of the user. Siri is “safe” for humans. Or, is 2 This paper concludes by questioning whether the control we have over Siri is real or an illusion that reinforces what Carey and Quirk (1989) called the “rhetoric of the electronic sublime.”